Screening and characterization of actinomycetes isolated from soybean rhizosphere for promoting plant growth - UMI FATMAWATI; ANJA MERYANDINI; ABDJAD ASIH NAWANGSIH; Aris Tri Wahyudi (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Fatmawati U, Meryandini A, Nawangsih AA, Wahyudi AT. 2019. Screening and characterization of actinomycetes isolated from soybean rhizosphere for promoting plant growth. Biodiversitas 20: 2970-2977. Actinomycetes which colonized plant rhizosphere has a vital role in improving plant growth by producing Indole-3-Acetic Acid (IAA). The aim of this study was to evaluate the potency of actinomycetes isolated from soybean rhizosphere as promoter agents for plant growth in vitro. Fifty actinomycetes isolates were successfully isolated from soybean rhizosphere. Based on the colorimetric methods, 35 isolates can produce IAA in various concentration, in the range of 0.46-30.6 mg/L. Seed germination assay using Ragdoll methods revealed that 26 isolates significantly promoted germination parameters, including the hypocotyl and the radicular length, the number of the lateral roots, and dry weight of the plant. Also, 14 from 26 isolates showed phosphate solubilizing activity in different phosphate-solubilizing index ranging from 1.25-2.62. Eight isolates were able to grow in N-free medium, indicating that these isolates have the ability in fixing nitrogen. Out of 23 from 26 isolates were detected to produce siderophore. All the tested isolates show chitinase production except ASR 55. Based on the observed parameters, it showed that there are four potential isolates (ASR 46, ASR 58, ASR 75 and ASR 76) as promising plant-growth promoters, phosphate solubilizer, nitrogen fixer, siderophore and chitinase producer. Based on the result of 16S rRNA sequence analysis, four potential isolates were identified as Streptomyces spp. in different taxa of strains and species.